Invasive social wasp learning abilities when foraging in human modified environments - Moreyra, Sabrina Natalia (2025)
The eusocial wasp Vespula germanica has successfully colonised diverse habitats worldwide. This study analyses whether V. germanica can learn to associate their own actions with food availability while foraging in human altered environments by using a Y-maze. We recorded the time taken by wasps to enter the device through a funnel in five consecutive visits; which changed its position randomly on each visit. Initially, food was placed in the funnel in the first two visits, while on the subsequent three visits, the resource was only offered after the wasp entered the device through the funnel. Our results showed that foragers chose the funnel to enter the Y-maze in search of food. Interestingly, on successive visits, when no food was offered, foragers learned to enter the device more rapidly. In sum, the present research reveals that these wasps exhibit diverse learning capabilities, sug- gesting that their responses can be modified by the consequences they experience. This is the first study to show empirical evidence of learning processes related to changes in motor responses associated with rewarding out- comes in V. germanica. This experimental research contributes to confirming the behavioural plasticity of this species, which could have facilitated its worldwide invasiveness.